Where Has Maine Been? Where is Maine Going? Taking the Long View of Maine’s Policy Context - Silka, Linda (Maine Policy Review, 2016)
Linda Silka initiates what we hope will become a regular MPR column, which looks forward and looks back at policy issues in Maine. In this piece, she reflects on discussions she had with Aram Calhoun, Andy Coburn, Carla Dickstein, and Evan Richert.
Keywords: Maine; public policy